The detection of potential carcinogenic PAH using HPLC procedure in two different smoked fish, case Study: Istanbul/Turkey - (:unkn) unknown (My University, 2010)
Bu çalışmada, 24 adet dumanlanmış balıkta potansiyel karsinojenik olan PAH’lar incelenmiştir. Salmon ve gökkuşağı alabalığı numuneleri likit kromatografi (HPLC) metoduyla analiz edilmiştir. Hiçbir dumanlanmış balık numunesinde güçlü karsinojenik ve gıda kodeksinde üst limiti belirtimiş bir PAH olan Benzo(a)pyrene’e rastlanmamıştır. Ancak yine karsinojenik potansiyeli bulunan benzo(a)antrecene, benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(g,h,i)perylene, dumanlanmış balık numunelerinde tespit edilmiştir. Balık yağı ve toplam PAH miktarları doğru orantılıdır. Dumanlanmış salmon balığının yağ oranı dumanlanmış gökkuşağı alabalığından fazladır. Ayrıca dumanlanmış balıkların toplam PAH miktarları arasında farklılıklar da saptanmıştır. Bu durum geleneksel fırında dumanlanmış örneklerin, dumanı homojen biçimde alamamasından kaynaklanmaktadır.

In this study, 24 samples of smoked fish products were analysed in order to investigate the levels of the potently carcinogenic PAHs. Salmon and rainbow trout samples were tested with a liquid choromatographic (HPLC) method. In none of the smoked fish products benzo(a)pyrene, one of the potential carcinogenic PAH compounds limited in food codex alimentarious was detected. However, benzo(a)antrecene, benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(g,h,i)perylene, compounds which could be carcinogenic for humans, were detected in the smoked samples. There is a significant correlation between the fish fat and the total PAHs level. Consequently the average fat contents of the smoked salmon were significantly higher than that of the smoked rainbow trout. It was also detected that the total PAH amount variations of the smoked fish samples were due to the non-homogenous smoke dispersion in the traditional ovens and it was difficult to obtain homogenous smoked fish products from traditional ovens.
İki farklı füme balıkta örnek olay incelemesi için HPLC prosedür kullanmıyla potansiyel kanserojen PAH tespiti: İstanbul / Türkiye
Keywords: Balıkçılık; Zooloji